Effects of modern technology (exergame and virtual reality) assisted rehabilitation vs conventional rehabilitation in patients with Parkinson's disease: a network meta-analysis of randomised controlled trials. (December 2022) - Chuang, Chieh-Sen; Chen, Yen-Wen; Zeng, Bing-Yan; Hung, Chao-Ming; Tu, Yu-Kang; Tai, Yi-Cheng; Wu, Yi-Cheng; Hsu, Chih-Wei; Lei, Wei-Te; Wu, Shey-Lin; Stubbs, Brendon; Carvalho, Andre F.; et al.
Abstract: Background: Modern technological applications, including exergames and virtual technology-assisted rehabilitation (VTAR) programmes, are promising for Parkinson's disease (PD) rehabilitation. However, evidence regarding their efficacy for rehabilitation is inconclusive. Objectives: This network meta-analysis (NMA) investigated the efficacy of exergames and VTAR on gait and balance outcomes and acceptability for patients with PD. Data sources: ClinicalKey, Cochrane CENTRAL, Embase, ProQuest, PubMed, ScienceDirect, Web of Science and ClinicalTrials.gov. Study selection: Randomised controlled trials (RCTs) investigating changes in gait or balance parameters were included in this study. Study appraisal and synthesis methods: In the NMA, standardised mean differences with 95% confidence intervals were calculated using a frequentist model. GRADE ratings were used to evaluate the quality of evidence in this study. Results: Twenty-three RCTs with 949 participants were included. Exergames and VTAR were associated with significantly better improvements in balance and gait outcomes than usual treatment and other active control interventions. However, exergames were not associated with changes in depressive symptoms. The evaluation of acceptability results indicated that all exergames and VTAR were adequately tolerated, as indicated by the low drop-out rates. Limitations: Small sample sizes and heterogeneity were the key limitations of this study. Conclusion and implications of key findings: This NMA confirmed that exergames are associated with more favourable gait and balance outcomes in patients with PD compared with usual treatment and other active control interventions. GRADE ratings revealed that most direct, indirect and overall network evidence was of low to medium quality. Larger-scale studies with longer follow-up periods are warranted.